The Effect of population and migration on forest cover in Indonesia - Sunderlin, William D.; Resosudarmo, I.A.P. (1999)
The massive loss of quantity and quality of natural forest cover in Indonesia threatens an important source of foreign exchange and employment. Several studies and government policies indicate that population growth, particularly among small landholders, is the principal cause of deforestation. Although there is an element of truth to these studies and policies, they greatly oversimplify and distort the issue of Indonesian deforestation. This article evaluates "population-centered" (neo-Malthusian) explanations of forest cover change in Indonesia in the light of non-population-centered (non-Malthusian) evidence. The conclusion is that although population growth is an important part of of the explanantion of Indonesian deforestation, it should be seen as an i ntermediate variable, and not as an independent variable. The policy implication is that nonpopulation factors should receive greater attention in policy measures directed at controlling inappropriate deforestation